Misi Amanat Agung Tuhan Yesus Berdasarkan Injil Matius 28:18-20 Di Kalangan Hamba Tuhan Kota Pontianak Kalimantan Barat - Mahdalena, Mahdalena; Daliman, Muner; Wahyuni, Sri (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
The Great Commission is the Great commandment that is often called the Great Commission from the Lord Jesus before He ascended to heaven. The Lord Jesus is the commanding officer in His great mission. Being involved in the mission of the Great Commission is the obligation of every believer, especially for the Servant of God in the city of Pontianak, West Kalimantan. Where the implementation of the mission of the Great Commission has been carried out well, and needs to be maintained so that the purpose of the Great Commission itself can be carried out continuously, namely making the nation disciples of Christ, through the service of the Servant of God in the city of Pontianak, West Kalimantan.